Historical plant introductions predict current insect invasions - Bonnamour, Aymeric; Blake, Rachael E; Liebhold, Andrew M; Nahrung, Helen F; Roques, Alain; Turner, Rebecca M; Yamanaka, Takehiko; Bertelsmeier, Cleo (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Thousands of insect species have been introduced outside of their native ranges, and some of them strongly impact ecosystems and human societies. Because a large fraction of insects feed on or are associated with plants, nonnative plants provide habitat and resources for invading insects, thereby facilitating their establishment. Furthermore, plant imports represent one of the main pathways for accidental nonnative insect introductions. Here, we tested the hypothesis that plant invasions precede and promote insect invasions. We found that geographical variation in current nonnative insect flows was best explained by nonnative plant flows dating back to 1900 rather than by more recent plant flows. Interestingly, nonnative plant flows were a better predictor of insect invasions than potentially confounding socioeconomic variables. Based on the observed time lag between plant and insect invasions, we estimated that the global insect invasion debt consists of 3,442 region-level introductions, representing a potential increase of 35% of insect invasions. This debt was most important in the Afrotropics, the Neotropics, and Indomalaya, where we expect a 10 to 20-fold increase in discoveries of new nonnative insect species. Overall, our results highlight the strong link between plant and insect invasions and show that limiting the spread of nonnative plants might be key to preventing future invasions of both plants and insects.
Keywords: rostliny; Plants; nonnative insects; Insecta; nonnative plants; zavlečené druhy; Animals; invasion debt; hmyz; species flow; zvířata; Introduced Species; time lag